KEMAMPUAN BERPIKIR KRITIS DAN KREATIF DALAM PEMBELAJARAN IPA PADA SISWA MINU HIDAYATUN NAJAH TUBAN - Nurhaningtyas Agustin; Pradana, Akhmad Aji; Hafni, Nurlaili Dina (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The ability to think critically and creatively is one of the priority abilities that the millennial generation must have in the 21st century. Efforts to improve students' critical and creative thinking abilities have been found through various learning approaches and models. However, before choosing the right type of approach and learning model in science learning, teachers are required to carry out initial mapping of students' critical and creative thinking abilities so that the chosen learning approach and model is more optimal and efficient. This research aims to describe the level of critical and creative thinking abilities of fourth grade students in science learning at MINU Hidayatun Najah Tuban with a total of 32 students as participants. The research design used is quantitative, survey-based on data that has been collected through test sheet and documentation methods. As a result, even though science learning for grade IV students at MINU Hidayatun Najah Tuban has used student-centered learning, the students' critical thinking abilities are still in the low category. On the other hand, students' creative thinking abilities are considered to be good. Thus, not all learning approaches and models are suitable for improving students' critical and creative thinking abilities, especially in science learning. For this reason, before implementing certain learning approaches and models in science learning, it is recommended to measure students' initial abilities that will be developed so that teachers can choose learning approaches and models according to their needs.